Growth Factor Engineering Strategies for Regenerative Medicine Applications - Ren, Xiaochen; Zhao, Moyuan; Lash, Blake; Martino, Mikaël M.; Julier, Ziad (Frontiers in Bioengineering and Biotechnology, 2020)
Growth factors are critical molecules for tissue development as well as tissue repair and regeneration. Therefore, recombinant growth factors have raised a lot of hope for regenerative medicine applications. While using growth factors to promote tissue regeneration has widely showed promising results in pre-clinical settings, their success in the clinic is not a forgone conclusion. Indeed, translation of growth factors is often limited by their short half-life, rapid diffusion from the delivery site, and low cost-effectiveness. Trying to circumvent those limitations by the use of supraphysiological doses has proven to lead to serious side-effects in many cases and therefore innovative technologies are required to improve growth factor-based regenerative strategies. In this review, we present protein engineering approaches seeking at improving growth factor delivery and efficacy while reducing doses and side-effects. We focus on engineering strategies seeking at improving affinity of growth factors for biomaterial carriers or the endogenous extracellular matrix. Then, we discuss some examples aiming at increasing growth factor stability and bioactivity, and propose new lines of research that the field of growth factor engineering for regenerative medicine may adopt in the future.